Library buildings around the world - Werner, Andreas J. (2014)
Library Buildings around the World" is a survey based on researches of several years. The objective was to gather library buildings on an international level starting with 1990. The parts Germany, France, United Kingdom, United States have been thoroughly revised, supplemented and completed for this 2nd edition. A revision of the other countries is planned for the next edition.